Brain network changes in adult victims of violence - Shymanskaya, Aliaksandra; Kohn, Nils; Habel, Ute; Wagels, Lisa (Frontiers in Psychiatry, 2023)
Introduction: Being exposed to violence can affect mental health severely. The effects are associated with changes in structural and functional brain networks. The current study aimed to investigate brain network changes in four large-scale brain networks, the default mode network, the salience network, the fronto-parietal network, and the dorsal attention network in victims of violence and non-victimized control subjects. Methods: The control group (n=32) was matched to the victim group (n=32) by age, gender, and primary psychiatric disorder. Sparse inverse covariance maps were derived from functional resting-state measurements and from T1 weighted structural data for both groups. Results: Our data underlined that mostly the salience network was affected in the whole sample of victims. In victims with a current psychiatric diagnosis, the dorsal attention network was mostly affected underlining the potential role of psychopathological alterations on attention-related processes. Conclusions: The results showed that victimized individuals demonstrated significant differences in all considered networks, both within- and between-network.